(untitled) (LACCEI, 2024)
The objective of this research was to determine the behavior of the physical and mechanical properties of adobe with the addition of sugarcane bagasse (BCA), Morrope 2022, using an applied methodology and experimental design. The sample consisted of 195 adobe units and 10 walls with the addition of (BCA) in dosages of 0%, 0.5%, 1.0%, 2% and 3%, designated for tests such as absorption, suction, dimensional variation, warping, resistance to wear by dripping, compressive strength in cubes and walls laboratory forms were used to collect data from these tests. The results showed that the absorption and suction increased as the (BCA) content increased having an increase of 31.25% and 126.67% respectively, the dimensional variation and warping decreased with the incorporation of (BCA) having more balanced values with the dosage of 2.0% of (BCA), with a dimensional variation of 0.53% in length, 0.70% in length, 1. 10% of height and a warping of 7.20 mm, the depth of perforation by erosion decreased by 30.94% and 47.67% with the dosages of 2.0% and 3.0% respectively, which exceeded the test, likewise, the optimum compressive strength was obtained with the 2.0% of (BCA), increasing by 48.96% for adobe cubes and 23.85% for adobe walls with respect to the standard adobe. It was concluded that the optimum dosage of (BCA) is 2%, improving both the physical and mechanical properties of the adobe